Empowering Indonesia's Local Brands: A Case Study on Ruaya’s Digital Branding and Marketing - Herfini, Dewi Diastuti; Iranti, Tasya Putri; Nadhifah, Yassela Luqi (Institut Komunikasi dan Bisnis LSPR, 2024)
This study highlights how Public Relations (PR) practitioners assist Indonesia's local Micro, Small, and Medium Enterprises (MSMEs) in the souvenir printing business for various needs. The products created by the local MSME named Ruaya are used by their clients to design digital campaigns aimed at developing better branding strategies and increasing customer awareness in marketing efforts.